NEW COLONIZATION IN THE ISLAMIC WORLD - Muhibudin Muhibudin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
In recent times, the dynamics of colonization have evolved beyond the conventional understanding of territorial conquests and dominations. This article delves into the phenomenon of "new colonization" in the Islamic world, focusing on its multifaceted manifestations and implications. By leveraging both qualitative research methodologies, the study uncovers the socio-political, economic, and cultural shifts induced by these neo-colonial practices. Drawing from primary sources, as well as secondary data like trade patterns and political alliance metrics, the article reveals a nuanced landscape of influence and control. Key findings suggest that new colonization in the Islamic world is largely characterized by economic dependencies, strategic geopolitical alliances, and cultural infiltrations. The ramifications of this are vast, affecting the very fabric of societies within the Islamic world, including their political autonomy, economic sovereignty, and cultural identity. The article emphasizes the necessity for increased awareness and proactive strategies to navigate and negotiate these neo-colonial forces.